2014
DOI: 10.1242/jcs.152520
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Yemanuclein is a cohesin and synaptonemal complex associated protein

Abstract: Meiosis is characterized by two chromosome segregation rounds (meiosis I and II), which follow a single round of DNA replication, resulting in haploid genome formation. Chromosome reduction occurs at meiosis I. It relies on key structures, such as chiasmata, which are formed by repair of double-strand breaks (DSBs) between the homologous chromatids. In turn, to allow for segregation of homologs, chiasmata rely on the maintenance of sister chromatid cohesion. In most species, chiasma formation requires the prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…It is plausible that this feature might reflect sex differences in chromatin structure at the LN2 locus or in the repertoire of binding transcription factors involved in sex determination. The speculations proposed here for the LN2 enhancer of Sxl would be akin to the genomic specializations described for general sex determination in plants and animals including Drosophila [43][44][45]. In any case, it seems that the mechanisms that underlie unstable enhancer expression are diverse but not unspecific.…”
Section: Discussionmentioning
confidence: 65%
“…It is plausible that this feature might reflect sex differences in chromatin structure at the LN2 locus or in the repertoire of binding transcription factors involved in sex determination. The speculations proposed here for the LN2 enhancer of Sxl would be akin to the genomic specializations described for general sex determination in plants and animals including Drosophila [43][44][45]. In any case, it seems that the mechanisms that underlie unstable enhancer expression are diverse but not unspecific.…”
Section: Discussionmentioning
confidence: 65%
“…Previous work with c(3)G 68 heterozygotes found no changes in recombination compared to wild-type controls (Miller 2020). However, c(3)G 1 heterozygotes have been reported to exhibit increased recombination in some genetic intervals (Hinton 1966;Meyer et al 2014). It is also possible that this variation in recombination phenotype may be the effect of minor variations in genetic background: Hinton assessed X chromosome recombination using different multiply marked X chromosomes and showed that recombination was not consistently altered in c(3)G 1 heterozygotes compared to controls when different X chromosomes were tested (Hinton 1966).…”
Section: Resultsmentioning
confidence: 95%